BLOOD PRESSURE CHANGES IN AFRICAN MALES DURING APPLICATION FOR ASYLUM STATUS IN ITALY: A PILOT STUDY. (June 2018) - Tavilla, R.; Scali, E.; Galanti, G.; Boddi, M.; Modesti, P.A.
Abstract: Objective: The Central Mediterranean route from Libya to Italy has become the major port of entry to Europe for migrants and refugees. In Italy few studies analysed health of asylum seekers, being mainly focused on infectious diseases. The aim of the present study was to explore cardiovascular risk factors of young asylum seekers during their first phase of residence in Italy. Design and method: Cross-sectional study performed on male African migrants, aged 18–35 years, during the period of application for asylum status in Prato, Italy. Subjects were classified in two groups according to their months of stay in Italy. Variables (Table 1) were measured with validated instruments according to guidelines. The relationship with months of stay in Italy (independent variable) was investigated with stepwise linear regression. Results: Subjects characteristics are reported (Table 1). After 6 months, 11 subjects had impaired fasting glucose (FG > 100 mg/dL) (3 in the < 6mo Group) (RR 3.4; 95%CL 1.0 to 11.5). The significant increase of systolic BP (months as the independent variable) was selected at stepwise multivariable adjusted linear regression (B 0.154;95%Cl 0.003 to 0.305, p = 0.046).https://services.aimgroup.eu/ASPClient/files/3647/Abstract/584_20180112140808.jpg Figure. No caption available. Conclusions: The syndromic surveillance system now active in immigration centres in Italy is mainly focused on infectious diseases. When considering the importance of hypertension for African descendent living in Europe, changes of CV risk factors in the new environment probably need more attention.